2019
DOI: 10.1007/s10967-019-06786-1
|View full text |Cite
|
Sign up to set email alerts
|

Trapping measurements of volatile iodine by sand bed and metallic filters

Abstract: A series of experimental tests were performed to measure the efficiency of volatile iodine trapping on sand bed filters and metallic filters. These filtering media are used in French nuclear power plants to mitigate releases in case of severe accident. The results show that molecular iodine is more easily trapped than methyl iodide due to its high chemical affinity with stainless steel or with silver and cesium cations included in the filter medium. For methyl iodide, the trapping efficiency is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…These rates are compatible with previous publications [32,33,34] on iodine interaction with steel as they are from one to two orders of magnitude higher than the ones expected for electro-polished steel (and for which the interaction of gaseous iodine is expected to much be slower). It is also compatible with the first part of this work [6] for which it was found that, at 100°C and 35% RH, gaseous I2 was retained on the MF with a DF ~ 10 (i.e. 90% retention in 4 hours).…”
Section: Effect Of the Metallic Filter On Csi And Iox Aérosols Décomp...supporting
confidence: 91%
See 2 more Smart Citations
“…These rates are compatible with previous publications [32,33,34] on iodine interaction with steel as they are from one to two orders of magnitude higher than the ones expected for electro-polished steel (and for which the interaction of gaseous iodine is expected to much be slower). It is also compatible with the first part of this work [6] for which it was found that, at 100°C and 35% RH, gaseous I2 was retained on the MF with a DF ~ 10 (i.e. 90% retention in 4 hours).…”
Section: Effect Of the Metallic Filter On Csi And Iox Aérosols Décomp...supporting
confidence: 91%
“…1) installed on the French NPPs is a PALL® Corporation product [4]. It consists of 92 filtering elements of 800 mm length and 60 mm diameter each [6,11], with a total filtration geometrical surface of 33 m2 These filtering elements, called "cartridges", are made, from the internal to the external parts, by: (1) a perforated internal grid; (2) a metallic weaved supporting layer; (3) a first filtering metallic medium (PFM FH 200); (4) a second filtering medium (PFM 40) and (5) a metallic weaved protective layer (Cf. left parts of Fig.…”
Section: Description Of the Geometry Of The Metallic Filter And Sand ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The PERSeE f acilky [20,22] was used in order to extrapolate the behavior of some selected zeolitic sorl'nts towards the capture of methyl iodide at semi-pilot scale, using conditions closer to severe nuclear accident (relative humidity, y-radiation, temperature). A general scheme of this facility is given in Figure S3 (see ESI).…”
Section: Retention Properti Es From Semi Pilot-scale Experiments: Test Bench 3 (Persee)mentioning
confidence: 99%
“…Attention was paid to ensure a good dispersion of the zeolitic material within the sand in the sample holder. Preliminary studies have shown that the used sand is totally ineffective for the retention of labelled methyl iodide (DF = 1 [20,22]). The different materials to be tested were placed in the upstream stage, giving the possibility to test simultaneously f< ur different solid mixtures {tested zeolite + sand} (Figure 1).…”
Section: Retention Properti Es From Semi Pilot-scale Experiments: Test Bench 3 (Persee)mentioning
confidence: 99%